2018
DOI: 10.3390/ijms19123929
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Fish Models to Elucidate Skin Cancer Pathogenesis and Impact the Discovery of New Therapeutic Opportunities

Abstract: Animal models play important roles in investigating the pathobiology of cancer, identifying relevant pathways, and developing novel therapeutic tools. Despite rapid progress in the understanding of disease mechanisms and technological advancement in drug discovery, negative trial outcomes are the most frequent incidences during a Phase III trial. Skin cancer is a potential life-threatening disease in humans and might be medically futile when tumors metastasize. This explains the low success rate of melanoma th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 169 publications
(178 reference statements)
0
14
0
Order By: Relevance
“…It was shown that the genetic hybrids of the pigmented platyfish ( Xiphophorus maculatus ) and the non-pigmented swordtails ( Xiphophorus helleri ) spontaneously develop melanoma. This model is one of the earliest animal cancer models [10,11]. Another example is medaka ( Oryzias latipes ), a small freshwater fish which has helped to uncover new aspects of cancerogenesis, again mostly in melanoma pathogenesis [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the genetic hybrids of the pigmented platyfish ( Xiphophorus maculatus ) and the non-pigmented swordtails ( Xiphophorus helleri ) spontaneously develop melanoma. This model is one of the earliest animal cancer models [10,11]. Another example is medaka ( Oryzias latipes ), a small freshwater fish which has helped to uncover new aspects of cancerogenesis, again mostly in melanoma pathogenesis [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…This model is one of the earliest animal cancer models [10,11]. Another example is medaka ( Oryzias latipes ), a small freshwater fish which has helped to uncover new aspects of cancerogenesis, again mostly in melanoma pathogenesis [10,12]. Zebrafish ( Danio rerio ) has gained the most attention as a robust animal for studying development and disease.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted gelatins from fish skin are the main ingredients of the gelatin films which are considered as a new environmentally friendly material [1][2][3]. Fish skin is also typically used as an effective drug-screening biological model, enabling us to deeply understand the human skin cancer [4][5][6]. Furthermore, for most fish species, their skins are covered by a large number of fish scales.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers introduced a plethora of animal models, such as zebrafish, rabbits, rats, dogs, pigs, goats, cattle and monkeys [ 22 , 23 , 24 , 25 , 26 ]. To be accepted as a valuable preclinical model, however, a scoring system should guarantee their careful selection, by reflecting face validity, complexity and predictability of a disease [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%